2020
DOI: 10.1126/science.abb3763
|View full text |Cite
|
Sign up to set email alerts
|

Diet posttranslationally modifies the mouse gut microbial proteome to modulate renal function

Abstract: Associations between chronic kidney disease (CKD) and the gut microbiota have been postulated, yet questions remain about the underlying mechanisms. In humans, dietary protein increases gut bacterial production of hydrogen sulfide (H2S), indole, and indoxyl sulfate. The latter are uremic toxins, and H2S has diverse physiological functions, some of which are mediated by posttranslational modification. In a mouse model of CKD, we found that a high sulfur amino acid–containing diet resulted in posttranslationally… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
110
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 136 publications
(111 citation statements)
references
References 64 publications
1
110
0
Order By: Relevance
“…However, it should be noted that a recent study of a mouse model of CKD has shown that a diet of sulfurcontaining amino acids reduced uremic toxin production through inhibition of the enzyme tryptophanase. 18 This issue of the Journal of Renal Nutrition features another article on the use of probiotic supplements in end-stage kidney disease, specifically patients on peritoneal dialysis. In their randomized controlled trial, Pan et al 19 evaluated 166 patients on peritoneal dialysis randomly assigned to either a control group or a daily dose of probiotics for 2 months and found decreases in the levels of hs-CRP and IL-6 in the intervention group.…”
mentioning
confidence: 99%
“…However, it should be noted that a recent study of a mouse model of CKD has shown that a diet of sulfurcontaining amino acids reduced uremic toxin production through inhibition of the enzyme tryptophanase. 18 This issue of the Journal of Renal Nutrition features another article on the use of probiotic supplements in end-stage kidney disease, specifically patients on peritoneal dialysis. In their randomized controlled trial, Pan et al 19 evaluated 166 patients on peritoneal dialysis randomly assigned to either a control group or a daily dose of probiotics for 2 months and found decreases in the levels of hs-CRP and IL-6 in the intervention group.…”
mentioning
confidence: 99%
“…Although promising, diet and SCFA based AKI therapy should be investigated more carefully given evidence for potential deleterious effects such as immune cell activation, T cell-mediated ureteritis and hydronephrosis (14). Diet-based posttranslational modifications of gut microbiota proteome and metabolites should be further explored to understand effects on AKI pathophysiology (12). Since reduced diversity of gut microbiota occurs in kidney transplantation recipients, elucidating the effect of gut microbiota on AKI could also have significant implications for allografts (15).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, in vitro SCFA treatment was found to modulate the inflammatory process by decreasing dendritic cell maturation and inhibiting CD4 and CD8 T cell proliferation and could be a potential mechanism through which gut microbiota interact and modulate T cell functions in vivo (10). Recent data demonstrated that diet can induce posttranslational modifications to the microbial proteome that in turn affects microbial metabolite production and ultimately kidney function (12). Lack of microbes in GF mice has also been shown to impact Treg cell differentiation due to absence of SCFAs production (13).…”
Section: Mechanism Of Gut Microbiota-immune System Interactionsmentioning
confidence: 99%
“…Considering this, it could be hypothesized that regulating the intestinal microbiota can lower blood pressure, ameliorate kidney disease, and prevent complications in patients with CKD. Intervening measures (e.g., increasing fiber intake, rational use of antibiotics [106,107], and therapeutic use of probiotics, prebiotics, and synbiotics) can restore the composition of intestinal flora and inhibit the accumulation of urotoxins in the blood [108,109]. According to the research of Lakshmanan et al [110], prebiotic gum acacia (GA) treatment restored the intestinal balance of CKD rats and relieves the inflammation of kidney tissue by increased production of butyrate, as well as its anti-inflammatory and antioxidant capacity.…”
Section: Gut Microbiota In Chronic Kidney Diseasementioning
confidence: 99%